Profesionalisme Tenaga Kepustakaan dalam Penguasaan Teknologi Informasi di Sman 12 Banda Aceh - Ismail Anshari; Yusnaini Yusnaini (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
This research is motivated by the lack of professional librarian in their field. There is only one librarian who actually comes from the library science department. The professionalism of the librarian is the implementation of library activities based on the ability of knowledge, experience, skills in managing and developing the implementation of work in the field of librarianship and other related activities independently. This research is entitled "Professionalism of Librarians in Mastering Information Technology at SMAN 12 Banda Aceh." This study aims to determine the professionalism of librarian in mastering information technology, obstacles faced by librarian professionalism in mastering information technology, and efforts of librarian professionalism in mastering information technology at SMAN 12 Banda Aceh. This type of research is a qualitative research. The research subjects were the head of the library, librarian and 2 students. Collecting data using the methods of observation, interviews, and documentation. The collected data is then analyzed through data collection, data reduction, data display, and drawing conclusions. To ensure the validity of this research data, using triangulation techniques sources and methods. The results of this study indicate that the professionalism of the librarian in mastering information technology at SMAN 12 Banda Aceh can be seen from the characteristics of the professionalism of the librarian. Barriers to the professionalism of the librarian in mastering information technology at SMAN 12 Banda Aceh, namely when the computer application started to crash and the wifi network had problems. Then the professionalism of the librarian in mastering information technology at SMAN 12 Banda Aceh is by working together in solving problems, especially in using computers.